2022
DOI: 10.1101/2022.01.25.477678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-uniform dystrophin re-expression after CRISPR-mediated exon excision in the dystrophin/utrophin double-knockout mouse model of DMD

Abstract: Duchenne muscular dystrophy (DMD) is the most prevalent inherited myopathy affecting children, caused by genetic loss of the gene encoding the dystrophin protein. There are currently four FDA-approved drugs for DMD that aim to restore expression of dystrophin by exon skipping using splice switching oligonucleotides. While these therapies require lifelong repeat administration, recent advancements in gene editing technologies have raised the possibility of achieving 'permanent exon skipping', and thereby curing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
1
2
1
Order By: Relevance
“…Treatment of mdx mice with PPMO conjugates resulted in a within-fiber uniform pattern of sarcolemmal dystrophin expression across dose levels ( Figure 5 ), consistent with our previous results. 9 This is in contrast to our observations in CRISPR-Cas9-treated muscle (see related article), 42 whereby dystrophin was expressed in a patchy manner. These findings point to a potential advantage of antisense oligonucleotide-mediated exon skipping over gene editing.…”
Section: Discussioncontrasting
confidence: 87%
“…Treatment of mdx mice with PPMO conjugates resulted in a within-fiber uniform pattern of sarcolemmal dystrophin expression across dose levels ( Figure 5 ), consistent with our previous results. 9 This is in contrast to our observations in CRISPR-Cas9-treated muscle (see related article), 42 whereby dystrophin was expressed in a patchy manner. These findings point to a potential advantage of antisense oligonucleotide-mediated exon skipping over gene editing.…”
Section: Discussioncontrasting
confidence: 87%
“…Multiple observations suggest that AAV gene therapies encoding nuclear-targeted cargoes are restricted to progenitor myonuclei following mRNA export, translation, and subsequent re-import of the encoded protein (13)(14)(15). Consistent with this, we observed that a limited number of myonuclei in WT C57BL/6 mice are functionally transduced by AAV packaged with a GFP transgene (Fig.…”
Section: Combining Nuclear Import and Export Signals Promotes Protein...supporting
confidence: 86%
“…Similar to endogenous mRNAs, gene therapy mRNAs are transcribed in successfully transduced nuclei, then exported and dispersed throughout the myonuclear domain ( 16, 36 ). Soluble and structural proteins translated from therapeutic mRNAs can then travel further, the latter perhaps being more restricted ( 14, 37 ), but nuclear-targeted proteins are trapped close to their progenitor domains ( 19, 38 ). Large nuclear-targeted proteins then have no way to passively exit the nuclear pore complex and are degraded within the nucleus over time ( 39 ), similar to other nucleocytoplasmic shuttling proteins ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation